The Position of Married Daughters in Adoption in the Ngada Tribe Indigenous Community (Study of Supreme Court Decision Number 407 K/Pdt/2019) - Natigor Daulay, R. Fahmi; Muhammad, Ade Sultan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research examines the position of married daughters in child adoption practices within the Ngada ethnic community through an analysis of Supreme Court Decision Number 407 K/Pdt/2019. Using normative legal research methods and a case approach, the study reveals that although the Ngada community adheres to a patrilineal system that traditionally prioritizes sons in child adoption, there exists an adaptive mechanism in the form of the concept